Genetics of Southeast Asian populations and interspecific hybrids of Fusarium spp. - Mohamed Nor, Nik Mohd Izham (Kansas State University, 2014)
Members of the genus Fusarium are widely distributed in many geographic regions of the world. This genus includes plant pathogens of many important cereal crops, e.g., wheat, maize, rice and sorghum, and of other native and economically important plants. From culture collections at Kansas State University and Universiti Sains Malaysia, strains from Southeast Asia, primarily from Malaysia and Thailand, associated with mango malformation disease, bakanae disease of rice, and stalk rot of sorghum were analyzed in sexual crosses and molecular diagnostics, e.g., Amplified Fragment Length Polymorphisms (AFLPs). Fusarium proliferatum was recovered from all three crops, with each crop also yielding some species unique to the crop, e.g. F. fujikuroi from rice, F. thapsinum from sorghum, and F. mangiferae from mango. These results are consistent with hypotheses that F. proliferatum has a wide host range while other species have much more limited host preferences. The absence from our samples of species associated with these diseases in other parts of the world suggests policies should be developed to reduce the chances of introduction of novel pathogens into Southeast Asia. Fusarium fujikuroi and F. proliferatum are closely related. They usually can be separated by sexual cross-fertility and DNA sequence analysis. However, some strains can cross irregularly and with poor fertility to produce viable interspecific hybrids. From a laboratory cross between F. fujikuroi FGSC8932 and F. proliferatum FGSC7615, 533 progeny were collected. These progeny were characterized for their AFLP genotype, mating type, gibberellic acid production, and pathogenicity on rice, onions, and apples. A recombination-based map from this interspecific cross was constructed. QTLs associated with gibberellic acid production, rice pathogenicity, and onion pathogenicity were identified. Gene segregation amongst the progeny of the F. fujikuroi × F. proliferatum cross was distorted towards F. proliferatum. Both novel and transgressive pathogenicity phenotypes were detected. Overall, this research demonstrates the potential threats that can result from an interspecific cross. These threats include pathogens with novel toxin profiles, new pathogenicity phenotypes, and more virulent strains. The variation observed among the progeny may enable isolation and characterization of genetic factors that have a role in pathogenicity, toxin production, and host specificity.
Keywords: Rice bakanae; Mango malformation; Sorghum; Fusarium proliferatum; Segregation distortion; Pathogenicity; Agriculture, General (0473); Genetics (0369); Plant Pathology (0480)